The Interpretation of Istighotsah Tradition Post Ndoro Purbo’s Grave Destruction in Yogyakarta - Dandung Budi Yuwono (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
Yogyakarta is known as a tolerans society, suddenly shocked by an incidence of thedestruction of the Ndoro Purbo’s grave, the 6th Sultan Hamengku Buwono’s grandchild, by irresponsible persons. In response to this incidence, a Nahdliyin (NU) community in Yogyakarta performs sacred rituals called an ‘istighotsah’. This is a qualitative research (case study) that aims to answer three problems: (1) how does NU in Yogyakarta look at the figure of Ndoro Purbo? (2) How do they interpret the acts of Ndoro Purbo’s grave destruction? And (3) Why does NU Yogyakarta perform a ritual ‘istighotsah’, and how do they interpret ‘istighotsah’? This study aims to explain the interpretation of NU members on the acts of Ndoro Purbo’s grave destruction, to understand the reasons of NU do ‘istighotsah’, and tofind the meaning of ‘istighotsah’ for NU members. Data was collected through observation, participant observation and in-depth interviews, while the interpretive data analysis is done using emic and ethical perspective. The study’s findings indicate that Ndoro Purbo was imaged as a figure of saint and known as a person with supernatural power. The Ndoro Purbo’s grave destruction was considered as a form of rudeness to the Javanese value, which is interpreted as violation of the Islamic values and a game of symbol, and it was considered as an act of wrongdoers. To fight such injustice among the NU members, they perform ritual‘istighotsah’ as an expression of a protest to God and a form of spiritual resistance during the difficult situation in facing disobedient or ‘visible sin’.